Pengaruh Kebiasaan Belajar dan Lingkungan Belajar Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Praktikum Akuntansi Jasa, Dagang Dan Manufaktur Siswa Kelas XI Akuntansi Keuangan Lembaga di SMK Negeri 2 Pariaman Tahun Ajaran 2018/2019 - Govin Afrinaval; Syamwil Syamwil (Jurnal Ecogen, 2019)
The purpose of this study was to determine the effect of Learning Habits and Learning Environments on accounting services, trade and manufacturing practicum subject Learning Achievement to Class XI Accounting SMK Negeri 2 Pariaman. Population was 106 students. Sample was 85 students selected by using sampling technique simple random sampling. Data were collected by questionnaires and documentation method. The method of analysis in this study was a quantitative analysis, the multiple linear regressions. The results showed that: 1) Learning Habits and Learning Environtment had a significant effect on student the learning achievement, (2) Learning Habits had a positive and significant effect on student learning achievment, (3) Learning Environment had a negative and significant effect on student learning achievement. Keywords: learning achievement, learning habits and learning environment